Aarachar - Meera,K.R (Kottayam: D C Books, 2019)
Award winning novel Aarachaar(Executioner) is a story based on the Indian culture of caste and religion. Set in Bengal, it tells the story of a family of executioners with a long lineage, beginning in the fourth century BC. The protagonist of the novel, Chetna, is a strong and tenacious woman who struggles to inherit this profession.
Keywords: Malayalam Novel